The consistency and complexity of accounting terminology in Croatian higher education system - Brozović, Mateja (Array, 2019)
Usually the most important role of language is to facilitate communication, which often proves challenging if the used terminology is inconsistent, complex or not understandable. These issues may especially affect specific language that is characteristic for a certain profession, particularly when the members of the profession communicate the message to the outsiders. Literature review suggests that the accounting terminology may sometimes be perceived as complex or incomprehensible, due to multiple changes and variations of accounting terms. Since there is a lack of research in the field of higher education, a research was conducted with the aim of analyzing accounting terminology used in the higher education institutions in Croatia. Both secondary and primary data were used in the analysis. The secondary data included accounting courses curricula of a sample of higher education institutions in Croatia, which were analyzed in order to explore the consistency of accounting terminology. In addition, the research was supplemented by collecting primary data using questionnaire on the attitudes of students about the complexity of accounting terminology. The analysis of accounting terms used in accounting courses curricula led to a conclusion that the analyzed courses, in most cases, are not harmonized regarding the terminology used. However, these results were expected from the previous research, that showed that the same applies for the Croatian regulatory accounting framework, which is why it was concluded that using different synonyms for the same accounting concepts may be beneficial for students. As for the students’ attitudes towards accounting terminology, the students who participated in the research mostly agree that the accounting courses often use different synonyms for the same concept.